Identification of novel mazEF/pemIK family toxin-antitoxin loci and their distribution in the Staphylococcus genus. Issue 1 (December 2017) - Bukowski, Michal; Hyz, Karolina; Janczak, Monika; Hydzik, Marcin; Dubin, Grzegorz; Wladyka, Benedykt
Abstract The versatile roles of toxin-antitoxin (TA) systems in bacterial physiology and pathogenesis have been investigated for more than three decades. Diverse TA loci in Bacteria and Archaea have been identified in genome-wide studies. The advent of massive parallel sequencing has substantially expanded the number of known bacterial genomic sequences over the last 5 years. In staphylococci, this has translated into an impressive increase from a few tens to a several thousands of available genomes, which has allowed us for the re-evalution of prior conclusions. In this study, we analysed the distribution ofmazEF /pemIK family TA system operons in available staphylococcal genomes and their prevalence in mobile genetic elements. 10 novelm azEF /pemIK homologues were identified, each with a corresponding toxin that plays a potentially different and undetermined physiological role. A detailed characterisation of these TA systems would be exceptionally useful. Of particular interest are those associated with an SCCmec mobile genetic element (responsible for multidrug resistance transmission) or representing the joint horizontal transfer of TA systems and determinants of vancomycin resistance from enterococci. The involvement of TA systems in maintaining mobile genetic elements and the associations between novelmazEF/pemIK loci and those which carry drug resistance genes highlight their potential medical importance.